2014
DOI: 10.1007/s11010-014-2124-1
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic response of checkpoint control proteins in hyperoxia: exposure to lower levels of oxygen induces genome maintenance genes in experimental baboon BPD

Abstract: Breathing high concentrations of oxygen (hyperoxia) causes lung injury and is associated with lung diseases such as bronchopulmonary dysplasia (BPD), respiratory distress syndrome (RDS) and persistent pulmonary hypertension of the newborns (PPHN). Hyperoxia (95–100%O2) causes DNA damage and growth arrest of lung cells and consequently cells die by apoptosis or necrosis. Although supplemental oxygen therapy is clinically important, the level and duration of hyperoxic exposure that would allow lung cells to reen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
1
9
0
1
Order By: Relevance
“…Previous studies have reported the critical roles of lung cell apoptosis in the occurrence and development of BPD [ 29 , 30 ]. In this study, we also investigated whether montelukast had an effect on lung cell apoptosis in vitro , and human type II alveolar epithelial cell line A549 was used in the present study to establish the lung cell injury model induced by hyperoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the critical roles of lung cell apoptosis in the occurrence and development of BPD [ 29 , 30 ]. In this study, we also investigated whether montelukast had an effect on lung cell apoptosis in vitro , and human type II alveolar epithelial cell line A549 was used in the present study to establish the lung cell injury model induced by hyperoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that CDC6 itself has a role in inhibiting apoptosis, complex CDC6 through its ATPase domain and apoptosis protease activating factor Apaf-1 to form stable, blocking the formation of apoptotic bodies [ 25 ]. Previous study indicated that cell apoptosis plays an important role in the occurrence and development process of premature BPD [ 26 ]. Our study showed that MALAT1 depletion in WI-38 cells induces cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Validation studies clearly demonstrated a robust, albeit with variable magnitude, accumulation of CTMC in the airspaces in BPD lung tissue. In a preterm baboon model of hyperoxia-induced lung injury leading to BPD-like phenotypes, microarray analysis of lung tissue identified increased expression of genes related to chromosomal maintenance, proliferation, and differentiation [50]. Additionally, and of note, in this model there appeared to be an increase in genes associated with the inhibition of inflammation.…”
Section: Transcriptomics Of Bpdmentioning
confidence: 99%